Implementasi Nilai Sila Pertama Pancasila Dalam Pengembangan Karakter Religius pada Siswi MTs Banat Tajul Ulum Brabo - Susiatik, Titik; Muryati, Sri; Hadi, Ag. Sutriyanto (Manalisih: Jurnal Penelitian, Sosial, dan Humaniora, 2023)
The first precepts of Pancasila, namely the Godhead, contain recognition of the existence of God as the creator of the universe and its contents. Therefore, as a human being who believes and believes that God can be realized in obedience to God by carrying out all His commands and away from all His prohibitions. It is proper for these values to be implanted in the younger generation, in which students of MTs Banat Tajul Ulum Brabo. The type of research is qualitative with phenomenological design. The subject as a key informant is the principal, while the complementary informant is the Deputy Principal of Curriculum Affairs, PPKN Teachers, and Representatives of Students. Data collection techniques used are, observation, documentation, and interviews, while data analysis techniques are used Interactive Miles and Huberman Models, including: data reduction, data presentation, and drawing conclusions, as well as the application of triangulation as the validity of data. Research Conclusions From the implementation of the first precepts of Pancasila in the development of religious characters in students of MTs Banat Tajul Ulum includes (three) forms of activities, namely: 1) The value of the creed is related to the faith of students towards God Almighty; 2) the value of worship as a practice of students to the teachings of God Almighty; and 3) Morals, namely the attitudes or behavior of students who reflect students who have morals.